Assisted automation: Three learning experiences in architectural robotics. (March 2017) - Llach, Daniel Cardoso; Bidgoli, Ardavan; Darbari, Shokofeh
Fueled by long-standing dreams of both material efficiency and aesthetic liberation, robots have become part of mainstream architectural discourses, raising the question: How may we nurture an ethos of visual, tactile, and spatial exploration in technologies that epitomize the legacies of industrial automation—for example, the pursuit of managerial efficiency, control, and an ever-finer subdivision of labor? Reviewing and extending a growing body of research on architectural robotics pedagogy, and bridging a constructionist tradition of design education with recent studies of science and technology, this article offers both a conceptual framework and concrete strategies to incorporate robots into architectural design education in ways that foster a spirit of exploration and discovery, which is key to learning creative design. Through reflective accounts of three learning experiences, we introduce the notions "assisted automation" and "robotic embodiment" as devices to enrich current approaches to robot–human design, highlighting situated and embodied aspects of designing with robotic machines.